Strategi Pembelajaran Inovatif Untuk Meningkatkan Pemahaman Dan Partisipasi Mahasiswa: Strategi Pembelajaran Inovatif Untuk Meningkatkan Pemahaman Dan Partisipasi Mahasiswa - Keba, Aprilini R. Dima; Kollo, Fredik L.; Funan, Irene; Atamukin, Kanisius K.K.; Bura, Sani Santia Ofani (Universitas Muhammadiyah Ponorogo, 2026)
The purpose of this study is to identify and analyze the effectiveness of innovative learning strategies in improving student understanding and participation in the Pancasila and Citizenship Education (PPKn) Study Program. Innovative learning strategies are approaches that emphasize interaction, collaboration, and the use of technology. This research approach uses a qualitative descriptive method with data collection techniques through observation, interviews, and questionnaires. The subjects of this study were lecturers and students and an active learning model was used. Data collection in this study used observation, questionnaires, interviews, and documentation. Data were processed and analyzed through data reduction, data presentation, and drawing conclusions. The results of the study indicate that project-based learning strategies, interactive discussions, and the use of digital technology in learning significantly improved conceptual understanding and active student participation in class activities